Les épisodes autonomes : écarts formels et narratifs dans The X-Files et Buffy The Vampire Slayer - Elaine Després (TV Series, 2019)
TV serial genres have evolved since the emergence of the medium, they are becoming more refined, more complex, more hybrid, responding to the growing demands and spectatorial skills of its audience. The genres thus allow the emergence of formulas, which are appropriated by creators, and from which they can build the matrix that will give their work its unique structure. Between the early canonical series and today’s great serials, the 1990s gave rise to several hybrid series, notably in the fantasy subgenre (for example, The X-Files and Buffy The Vampire Slayer), which combine serial episodes and larger seasonal story arc. At the heart of these series are stand-alone episodes, often the most appreciated, that move away from the matrix and propose fictional, narrative or transtextual innovations and games.